The Philippine islands, 1493-1803 explorations by early navigators, descriptions of the islands and their peoples, their history and records of the Catholic missions, as related in contemporaneous books and manuscripts, showing the political, economic, commercial and religious conditions of those islands from their earliest relations with European nations to the beginning of the nineteenth century, Vol. XLVI-1721-1739 - Blair, Emma Helen 1911; Robertson, James Alexander 1873-1939; Bourne, Edward Gaylord 1860-1908 (A.H. Clark Co., 1907)
The theme of the present volume is throughout the conquest of Manila by the British in 1762, and events consequent to it. The various accounts we have drawn from both Spanish and English sources, in order that we might present the matter from the standpoints of each nation, and we have aimed to give the story in great detail from as many points of view as possible. The subject must have special interest for Americans by reason of the operations of 1898. In some measure the captures by both the British and the Americans are analogous, because in each case it was rather a side demonstration than the main object of the war, and because of the ease with which it was accomplished. Here, however, the analogy ends, for British occupation was at the best precarious while it lasted, and made scarcely any headway outside of Manila; and while naturally the questions of religion, commerce, and civil affairs generally were discussed, nothing lasting was done. It may well be that the ease with which Manila was taken by the British gave the Filipinos some idea, though slight, of separation from Spain, or a desire for a larger degree of independence; although, in truth, all such ideas appeared to be effectively stifled with the strengthening power of the religious orders. Of special interest will [12]be found the operations of Anda y Salazar, a true patriot, though like the Count de Frontenac, of Canada, of a hasty and impetuous nature; and his contest with the incapable archbishop. It is to be noted throughout that all English dates are one day in advance of the Spanish dates, as the English had the same dates as the Portuguese, who reached the Orient by way of the Eastern route. This is a momentous period in many parts of the world.